MoS2 nanobelts-carbon hybrid material for supercapacitor applications - Khandare, Lina N.; Late, Dattatray J.; Chaure, Nandu B. (Frontiers in Chemistry, 2023)
The MoS2 nanobelts/Carbon hybrid nanostructure was synthesized by the simple hydrothermal method. The MoS2 nanobelts were distributed in the interlayers of Lemon grass-derived carbon (LG-C), provides the active sites and avoid restacking of the sheets. The structural and morphological characterization of MoS2/LG-C and LG-C were performed by Raman spectroscopy, X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy. The electrochemical measurements were studied with cyclic voltammetry, the galvanostatic charge-discharge method, and electrochemical impedance spectroscopy. The specific capacitance of MoS2/LG-C and LG-C exhibits 77.5 F g-1 and 30.1 F g-1 at a current density of 0.5 A g-1. The MoS2/LG-C-based supercapacitor provided the maximum power density and energy density of 273.2 W kg-1 and 2.1 Wh kg-1, respectively. Furthermore, the cyclic stability of MoS2/LG-C was tested using charging-discharging up to 3000 cycles, confirming only a 71.6% capacitance retention at a current density of 3 A g-1. The result showed that MoS2/LG-C is a superior low-cost electrode material that delivered a high electrochemical performance for the next generation of electrochemical energy storage.